Effect of Er3+ doping on structural, morphological and photocatalytical properties of ZnO thin films. (25th May 2018) - Bouhouche, S; Bensouici, F; Toubane, M; Azizi, A; Otmani, A; Chebout, K; Kezzoula, F; Tala-Ighil, R; Bououdina, M
Abstract: In this research work, structure, microstructure, optical and photocatalytic properties of undoped and Erbium doped nanostructured ZnO thin films prepared by sol-gel dip-coating are investigated. X-ray diffraction (XRD) analysis indicates that the deposited films crystallize within the hexagonal wurtzite-type structure with a preferential growth orientation along (002) plane. Morphological observations using scanning electron microscopy (SEM) reveal important influence of Er concentration; displaying homogeneous and dense aspect for undoped to 0.3% then grid-like morphology for 0.4 and 0.5%. UV/vis/NIR transmittance spectroscopy spectra display a transmittance over 70%, and small variation in the energy gap energy 3.263–3.278 eV. Wettability test of ZnO thin films surface ranges from hydrophilic aspect for pure ZnO to hydrophobic one for Er doped ZnO, and the contact angle is found to increase from 58.7° for pure ZnO up to 98.4° for 0.4% Er doped ZnO. The photocatalytic activity measurements evaluated using the degradation of methylene blue (MB) under UV light irradiation demonstrate that undoped ZnO film shows higher photocatalytic activity compared to Er doped ZnO films, which may be attributed to the deterioration of films'crystallinity resulting in lower transmittance.